Polyandry and paternity affect disease resistance in eusocial wasps. (16th July 2020) - Saga, Tatsuya; Okuno, Masaki; Loope, Kevin J; Tsuchida, Koji; Ohbayashi, Kako; Shimada, Masakazu; Okada, Yasukazu
Abstract: Polyandry (multiple mating by females) is a central challenge for understanding the evolution of eusociality. Several hypotheses have been proposed to explain its observed benefits in eusocial Hymenoptera, one of which, the parasite–pathogen hypothesis (PPH), posits that high genotypic variance among workers for disease resistance prevents catastrophic colony collapse. We tested the PPH in the polyandrous wasp Vespula shidai. We infected isolated workers with the entomopathogenic fungus Beauveria bassiana and quantified their survival in the laboratory. Additionally, we conducted a paternity analysis of the workers using nine microsatellite loci to investigate the relationship between survival and the matriline and patriline membership of the workers. As predicted by the PPH, nestmate workers of different patrilines showed differential resistance to B. bassiana . We also demonstrated variation in virulence among strains of B. bassiana . Our results are the first to directly support the PPH in eusocial wasps and suggest that similar evolutionary pressures drove the convergent origin and maintenance of polyandry in ants, bees, and wasps. Abstract : Sibling wasp workers with different fathers differed in their survival after a pathogen challenge, supporting the idea that worker genetic diversity from multiple mating by queens provides benefits through colony disease resistance. Our experiment, the first test of this hypothesis in eusocial wasps, suggests that convergently evolved multiple mating in wasps provides genetic diversity benefits similar to those observed in multiply mating ants and bees.